WHO´S AFRAID OF DEMOCRACY - Hayes, Christopher (La Sociología en sus Escenarios, 2009)
Abstract. Though only one data point, it suggests that people have a profound sense of economic fairness, that we are all, more or less, intuitive socialists. As far back as Edmund Burke, conservatives have suspected as much and feared democracy for that very reason. Read James Madison in the Federalist Papers and it’s clear that many of the Constitution’s undemocratic elements were designed to prevent the expropriation of wealth from an outnumbered elite. Resumen. Aunque solamente un punto de referencias, él sugiere que la gente tenga un sentido profundo de la imparcialidad económica, que somos todos, más o menos, los socialistas intuitivos. Desde Edmund Burke, los conservadores han sospechado tanto y la democracia temida por esa mismo razón. Leer a James Madison en los papeles del federalista y está claro que muchos de los elementos undemocratic de la constitución fueron diseñados para prevenir la expropiación de la abundancia de una élite excedida en número.